Pengaruh Pemasaran Produk Baitul Mal Wa Tamwil (BMT) dan Implementasinya Berbasis Digital di Pekalongan - Muh. Izza (Velocity: Journal of Sharia Finance and Banking, 2022)
The purpose of this paper is to examine the implementation of digital-based marketing of BMT products in Pekalongan. This theme departs from the gap that the digitalization trend has influenced business behavior in Islamic microfinance institutions (BMT). The type of this research is field research in three Islamic microfinance institutions in Pekalongan. The research approach of this study uses a phenomenological qualitative descriptive method. The results of this study, firstly, show that the marketing of financial institution products has used e-mobile applications through two work system patterns, namely (1) Unitary System Work Patterns with nine services (2) Unitary System Work Patterns through four services. Secondly, the implementation of this marketing through various digital media channels that are synergistic, linear, and practical-economically carried out in three steps, namely (1) Data Digitization (2) Creating and Utilizing Digital Media, and (3) Synergizing Data into Digital Media. Thirdly, services through digital products go through six processes, namely (1) account creation, (2) filling in personal data (3) attaching attachments, (4) data verification, (5) institutional confirmation, and (f) finishing.